DUA BELAS TEKNIK IKAT KONSTRUKSI KAYU PADA RUMAH VERNAKULAR TOLAKI - Putra Wijaya; Muhammad Zakaria Umar; Muhammad Arsyad (Laboratorium Jurusan Antropologi, Fakultas Ilmu Budaya, Universitas Halu Oleo, 2020)
The technique of binding wood construction in Tolaki vernacular houses tends to fade due to esotericism. This research is important as follows: (1) to uncover and preserve Tolaki's architectural identity in the form of wood-binding techniques; (2) to enrich the Southeast Sulawesi architecture literature in particular and Indonesian architecture in general. This research is intended to formulate the wood construction binding technique in Tolaki vernacular house. This research uses a case study method with a qualitative approach. Data sources consist of primary data and secondary data. This research uses triangulation data collection techniques. The method of data analysis is carried out by means of information organized, information and codefication studied, cases and contexts described, findings interpreted, and findings presented narratively. The study concluded that the construction of wood in the Tolaki vernacular house consisted of 12 (twelve) connective techniques as follows: first, peusu temomo, peusu kinalase, peusu pinewa’a, peusu pinepuhe, peusu niranggia, and peusu tundo ndowaea are included in the category of cross ties; second, peusu kinalili and peusu pinekalo are included in the category of dead cross ties; third, peusu pinepuhu, peusu sinemba, peusu mbekale, and peusu sinemba aso hara are included in the category of mobile cross ties.